(untitled) (International Journal of Engineering and Computer Science, 2017)
Biometric authentication is a security process that relies on the unique biological characteristics of an individual to verify that he is who is says he is. Biometric authentication systems compare a biometric data capture to stored, confirmed authentic data in a database. If both samples of the biometric data match, authentication is confirmed. Human hair consists of proteins, lipids, water, trace elements ,toxic elements, other elements and pigments. The composition of the elements may vary from one hair of one human to another human. the elements present in the hair can be consider for biometric authentication. the various elements in the hair can be calculated and this will be a part of a bio metric authentication. this can be highly useful in the smart cards In the future. The main component of hair is protein and amino acid. The percentage of elements in the hair may vary to each human being. This paper present the theoretical aspect of all the elements in the hair and how it can be used for biometric authentication.